2022
DOI: 10.1080/08897077.2022.2074602
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Changing Drinking and Receiving Alcohol-Related Care: Interviews with Veterans Health Administration Primary Care Patients who Indicated Interest but Did Not Enroll in An Alcohol Care Management Intervention Trial

Abstract: Background: Most people with alcohol use disorder do not receive treatment, and primary care (PC)-based management of alcohol use disorder is a key strategy to close this gap. Understanding PC patients’ perspectives on changing drinking and receiving alcohol-related care is important for this goal, particularly among those who decline alcohol-related care. This study examined perspectives on barriers and facilitators to changing drinking and receiving alcohol-related care among Veterans Health Administration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Barriers on the patient level are low knowledge of AUD pharmacotherapies [ 48 ], and the perception that AUD treatment is not effective [ 49 ]. Studies specifically focusing on individuals with AUD and medical comorbidities, highlight barriers such as the desire to handle alcohol-related problems independently, reluctance to abstinence-only-treatments, a perceived lack of integration between addiction care and medical care, and fear of stigmatisation [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barriers on the patient level are low knowledge of AUD pharmacotherapies [ 48 ], and the perception that AUD treatment is not effective [ 49 ]. Studies specifically focusing on individuals with AUD and medical comorbidities, highlight barriers such as the desire to handle alcohol-related problems independently, reluctance to abstinence-only-treatments, a perceived lack of integration between addiction care and medical care, and fear of stigmatisation [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of supplanted AUD pharmacotherapy in the COVID‐19 period may be related to low utilization pre‐COVID‐19 [23, 40, 51], but may also represent an opportunity to enhance AUD treatment use given the ongoing pandemic and its impact on health‐care. Numerous barriers to AUD treatment exist, including stigma, lack of patient‐perceived treatment need, limited knowledge regarding AUD treatment by patients and clinicians and limited perceived effectiveness of AUD treatment, among others [52, 53], and the decrease in treatment rates indicate that many barriers were further exacerbated by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of supplanted AUD pharmacotherapy in the COVID-19 period may be related to low utilization pre-COVID-19[23,40,51], but may also represent an opportunity to enhance AUD treatment use given the ongoing pandemic and its impact on health-care. Numerous barriers to AUD treatment exist, including stigma, lack of patient-perceived treatment need, limited knowledge regarding AUD treatment by patients and clinicians and limited perceived effectiveness of AUD treatment, among others[52,53], and the decrease in treatment rates indicate that many barriers were further exacerbated by the pandemic.Examining telehealth delivery of treatment for vulnerable patients, including those with AUD, is particularly important in the current context of the ongoing COVID-19 pandemic. Much chronic care management, including behavioral health, has shifted from in-person to telehealth care during COVID-19[12], and our study findings parallel broader changes reported during COVID-19[54].…”
mentioning
confidence: 99%